Measurement method and influencing factors of temperature and humidity of condensed flue gas based on in situ flue gas heat tracing. (May 2018) - Gao, Jianmin; Sun, Zhihao; Wang, Zhiqiang; Wang, Xin; Guan, Jian; Qi, Guoli; Wang, Zhongwei; Du, Qian; Qin, Yukun
Highlights: An in situ heating interlayer pumping device was proposed. The main operating parameters of the measuring device were optimized. The reliability of the device was verified by the positive and counter balance test. The uncertainty of measurement results were analyzed. Abstract: Condensing boilers are efficient for the utilization of natural gas. However, condensed droplets in flue gas are supercooled after condensation heat transfer, and direct contact devices cannot accurately measure the temperature of flue gas containing such droplets. Therefore, an in situ heating interlayer pumping device was designed. Experimental results showed that in situ heating interlayer pumping device can effectively filtered out the influence of supercooled droplets, the temperature of flue gas measured by the proposed device was about 3 °C higher than that measured by direct contact temperature measuring device; the device optimum flow rate was 0.35 L/min, optimum heat tracing temperature was in the range 100–140 °C; the effective reliability of the device was verified experimentally using the positive balance efficiency and the counter balance efficiency of 30-kW gas-fired condensing heat-transfer test platform.